Conductivity as a predictive parameter of hardness in groundwater and spring water of Costa Rica - Solís-Castro, Yuliana (2018)
The aim of the study is to determine the relations between conductivity with total hardness and calcium hardness in groundwater and spring water used as drinking-water sources in Costa Rica. Firstly, 1948 wells and 2699 springs evaluated between 2013-2015 were selected from the Drinking-Water Quality Control Program of the National Water Laboratory. Secondly, conductivity ranges were defined for wells from 50 µs/cm to 549 µs/cm, and 20 µs/cm to 499 µs/cm for springs. Based on the averages, the relation of conductivity with total hardness and calcium hardness were calculated for each type of water source. According to the results, the correlation coefficient (R2) between conductivity and total hardness was 0,9931 in wells and 0,9958 in springs. On the other hand, R2 between conductivity and calcium hardness was 0,9922 in wells and 0,9942 in springs. Calibration curves were applied in 20 wells and 20 springs drinking-water samples between 2016 to 2017. The results showed that conductivity (in normal situations) is a good indirect indicator for total and calcium hardness in groundwater and spring water. Conductivity measured in situ is recommended to estimate total and calcium hardness in groundwater and spring water.